2016
DOI: 10.18203/issn.2455-4510.intjresorthop20160712
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of locking plate fixation for proximal humerus fractures

Abstract: <p class="abstract"><strong>Background:</strong> The objective of the study was to evaluate functional outcome of open reduction and internal fixation with proximal humeral internal locking system (PHILOS) plate for proximal humerus fractures.</p><p class="abstract"><strong><span lang="EN-US">Methods:</span></strong><span lang="EN-US"> We reviewed 30 patients who underwent open reduction and internal fixation with PHILOS plate between the years 2010 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Edwards et al (22) reported that locking plate is highly superior over proximal humerus nailing in terms of both varus bending and torsional stability. In a study by Rohra et al (23) reporting the results of locking plate method for proximal humerus plate, overall complication rate was indicated as 20 percent. In our study also overall complication rate was found as 23.5 percent.…”
Section: Discussionmentioning
confidence: 99%
“…Edwards et al (22) reported that locking plate is highly superior over proximal humerus nailing in terms of both varus bending and torsional stability. In a study by Rohra et al (23) reporting the results of locking plate method for proximal humerus plate, overall complication rate was indicated as 20 percent. In our study also overall complication rate was found as 23.5 percent.…”
Section: Discussionmentioning
confidence: 99%
“…In young patients high energy trauma is most common cause, in elderly patients -trivial fall (due to osteoporosis) is most common cause [7] . Different techniques like closed reduction with K-wire, open reduction with fixation with bone sutures, Multi lock nail, Reverse shoulder replacement, Polaris nail have been developed [8] . Complications from above methods like cutout/backout of screws, avn, nail migration, rotator cuff impingment are present [9] .…”
Section: Introductionmentioning
confidence: 99%